'Post-Truths' of Public Memory: Art and Transitional Justice within Kenya's Reinvention of a Postcolonial State Edifice/Serikali. Issue 1 (4th August 2020) - Maingi, Donald
After Kenya had won its political independence, the authoritarian KANU government imposed a corrupt and authoritarian populist state upon the country, deploying a nationalist narrative that silenced alternative public memories. Kenyans then engaged in an ethno-political struggle for democratization, which fuelled cycles of ethnic violence. The capacity of Kenyans to 'come to terms with the past' was hampered by political elites manipulating ethnic violence and historical injustices for political ends. Such manipulative procedures gave rise to a politically sensitive national mood that thrives upon historical 'post-truths'. 55 years after Kenya obtained political independence, such populist renditions of Kenyan history, now serving to protect authoritarian state interests, have spurred Kenyan artists into activism. In their view, these populist narratives represent the public re-inscription of a localised legacy of political impunity, which, in fact, had crystallized during the botched Kenyan cases at the International Criminal Court (ICC ). Indeed, the victims of Kenya's traumatic 2007–8 post-election violence became victims all over again within this legal process as the government ensured that publicly funded domestic transitional justice mechanisms remained politically ineffective. This set a highly dangerous precedent, with the Kenyan government encouraging other African countries to withdraw from the Rome Statute – in a political climate more broadly marked by a global rise in populist nationalism. Such an international climate and mood has encouraged the elites to disparage internationally binding obligations upon the Kenyan state designed to strengthen its transitional justice mechanisms – particularly in dealing with historical injustices. Such popular local artists as Joseph Mbatia (alias Bertiers), Sebastian Kiarie and Michael Soi have however engaged directly with such powerful ethno-political renderings of populism, deploying increasingly pertinent public forms of ventriloquism. I argue that their art works, together with various other media programmes of political puppetry, offered the Kenyan public a futuristic unmasking of localised "post-truths" of public memory. This unmasking assumed the visual form of problematic political imaginaries, which the Kenyan populist state has in its turn sought to counter. These artists' recasting of the relationship between Kenya's modernity and its national trauma served to redefine their cathartic response to cycles of violence, which had involved a 'coming to terms with the past', by using humour to mimic the imaginary authoritarian populist State.